Answer:
[tex]\large\boxed{y=-4x^2+4x-3}[/tex]
Step-by-step explanation:
[tex]y=-4x^2-4x-3\\\\\text{Check for}\ (-1,\ -11):\\\\-11=-4(-1)^2-4(-1)-3\\-11=-4(1)+4-3\\-11=-4+4-3\\-11=-3\qquad\boxed{FALSE}\\===========================\\y=-4x^2+4x-3\\\\\text{Check for}\ (-1,\ -11):\\\\-11=-4(1)^2-4(1)-3\\-11=-4-4-3\\-11=-11\qquad\boxed{CORRECT}\\\\\text{Check for}\ (0,\ -3):\\\\-3=-4(0)^2+4(0)-3\\-3=-3\qquad\boxed{CORRECT}\\\\\text{Check for}\ (3,\ -27):\\\\-27=-4(3)^2+4(3)-3\\-27=-4(9)+12-3\\-27=-36+12-3\\-27=-27\qquad\boxed{CORRECT}[/tex]
[tex]===========================\\y=-4x^2-4x+3\\\\\text{Check for}\ (-1,\ -11):\\\\-11=-4(-1)^2-4(-1)+3\\-11=-4(1)+4+3\\-11=-4+4+3\\-11=3\qquad\boxed{FALSE}\\===========================\\y=4x^2-4x-3\\\\\text{Check for}\ (-1,\ -11):\\\\-11=4(-1)^2-4(-1)-3\\-11=4(1)+4-3\\-11=4+4-3\\-11=5\qquad\boxed{FALSE}[/tex]